2014
DOI: 10.1088/0004-637x/795/2/165
|View full text |Cite
|
Sign up to set email alerts
|

STRONG NEBULAR LINE RATIOS IN THE SPECTRA ofz∼ 2-3 STAR FORMING GALAXIES: FIRST RESULTS FROM KBSS-MOSFIRE

Abstract: We present initial results of a deep near-IR spectroscopic survey covering the 15 fields of the Keck Baryonic Structure Survey (KBSS) using MOSFIRE on the Keck 1 telescope, focusing on a sample of 251 galaxies with redshifts 2.0 < z < 2.6, star-formation rates 2 < ∼ SFR < ∼ 200 M yr −1 , and stellar masses 8.6 < log(M * /M ) < 11.4, with high-quality spectra in both H-and K-band atmospheric windows. We show unambiguously that the locus of z ∼ 2.3 galaxies in the "BPT" nebular diagnostic diagram exhibits a disj… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

132
1,204
13

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 657 publications
(1,349 citation statements)
references
References 135 publications
(253 reference statements)
132
1,204
13
Order By: Relevance
“…To verify this conclusion with our sample we show in Fig. 9 star-forming galaxies at z > 2 by Cullen et al (2014) (stars), star-forming galaxies at 2.0 < z < 2.6 by Steidel et al (2014) (filled circles), star-forming galaxies at redshifts z ∼ 3.5 by Maiolino et al (2008) (filled squares), star-forming galaxies with z ∼ 2 by Maier et al (2014) (crosses), and star-forming galaxies with z ∼ 3.4 by Troncoso et al (2014) (asterisks). The relation for galaxies with z ∼ 2.3 by Sanders et al (2015) is shown by thick yellow solid line.…”
Section: Stellar Mass -Metallicity Relationsupporting
confidence: 59%
See 4 more Smart Citations
“…To verify this conclusion with our sample we show in Fig. 9 star-forming galaxies at z > 2 by Cullen et al (2014) (stars), star-forming galaxies at 2.0 < z < 2.6 by Steidel et al (2014) (filled circles), star-forming galaxies at redshifts z ∼ 3.5 by Maiolino et al (2008) (filled squares), star-forming galaxies with z ∼ 2 by Maier et al (2014) (crosses), and star-forming galaxies with z ∼ 3.4 by Troncoso et al (2014) (asterisks). The relation for galaxies with z ∼ 2.3 by Sanders et al (2015) is shown by thick yellow solid line.…”
Section: Stellar Mass -Metallicity Relationsupporting
confidence: 59%
“…The mass-metallicity relation by Tremonti et al (2004) is often used as a benchmark for comparisons with similar relations obtained for low-z and high-z galaxies (e.g. Lee et al 2006;Maiolino et al 2008;Amorín et al 2010;Manucci et al 2010;Maier et al 2014;Steidel et al 2014;Zahid et al 2011Zahid et al , 2012Zahid et al , 2013Zahid et al , 2014a. However, we note that Tremonti et al (2004) selected all star-forming galaxies, including galaxies with low-excitation H ii regions, while only galaxies with high-excitation H ii regions are present in high-z samples.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations